Locoregional Recurrence after Biochemical Incomplete Response in Differentiated Thyroid Cancer Patients: Insights into Influencing Clinicopathological Factors and the Potential Role of 18F-FDG PET/CT - Elahmadawy, Mai Amr; Ali, Ismail Mohamed; Nasr, Ibrahim Mansour; Talaat, Omnia (World Journal of Nuclear Medicine, 2025)
The aim of this study was to evaluate the clinicopathological factors and stimulated thyroglobulin (Tg) course related to the occurrence of locoregional recurrence (LRR) in differentiated thyroid cancer (DTC) patients with biochemical incomplete response (BIR) as well as the value of fluorine-18 fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) in these patients.A total of 253 DTC adult patients initially treated with total thyroidectomy and iodine-131 (RAI-131) ablation and showed BIR on follow-up were enrolled in the study. All clinical, laboratory, pathological, radiological, and follow-up data were retrieved from their records.Seventy-three out of the 253 BIR patients developed LRR during follow-up with the median time to recurrence of 27 months. In all, 61.6% of those who developed LRR were females, 78.1% were papillary thyroid carcinomas, 35.6% had initial regional nodal deposits, and the primary tumors were T2 and T3 in 78.2% of these patients (p < 0.05). The median Tg level for those who developed LRR compared with those who remained free was 18 versus 17 ng/mL, respectively, at 6 months of follow-up. Meanwhile, on further 1-year follow-up, the median value spontaneously increased for the positive group to 37.6 ng/mL and decreased for those who remained free to 3 ng/mL. Eighty percent of the patients with a rising course of Tg level developed structural LRR (p < 0.001). 18F-FDG PET/CT showed the highest sensitivity and negative predictive value (NPV) of 100% in the detection of LRR compared with sensitivity values of 92.86 and 85.71% and NPV of 99.58 and 99.17%, respectively, with ultrasound (US) and RAI-131 scan. Meanwhile the highest specificity and positive predictive value (PPV) of 100% were observed noted with RAI-131 compared to specificity values of 99.16 and 99.58% and PPV of 87.50 and 92.86% with PET/CT and US, respectively. A cutoff point (SUVmax of 3.65) was successfully marked to discriminate those positive versus negative LRR with sensitivity and specificity of 100% and p-value of less than 0.001.Structural LRR after BIR appears to be more commonly associated with worse clinicopathological parameters and the incremental Tg levels serve as an indicator of its higher incidence. 18F-FDG PET/CT has been shown to be a valuable diagnostic tool rather than a prognostic one in these patients.
Keywords: BIR; thyroid cancer; locoregional recurrence; Tg; PET/CT